The role of chronic cervicitis and disorders of local immunity of the cervix in the etiology of undeveloped pregnancy - Anna I. Fedorova; Evgenii I. Novikov; Ekaterina A. Grin; Andrei E. Myagkov; Anna I. Koptelova (IP Berlin A.V., 2021)
Aim. To determine the role of chronic cervicitis and violations of local immunity of the cervix in the etiology of miscarriage of the first trimester, as well as to justify the necessary scope of examination for timely therapeutic and preventive measures. Materials and methods. The results of a prospective and retrospective study of 225 women with undeveloped pregnancy who were admitted to a gynecological hospital are presented. All women received microscopic, cultural, and molecular genetic (PCR), studies of vaginal and cervical canal discharge, cytological studies of scrapings from the cervical canal and cervix, studies of the structure of cervical mucus and its immunoglobulin A, and pathomorphological studies of the fetal egg. According to the results of the pathomorphological examination of the abortion material in combination with the clinical data, the examined patients were divided into 2 groups. Group 1 included 95 women with bacterial infection of the fetal egg, group 2 90 women with viral infection of the fetal egg. As a control group, 40 women with normal progressive pregnancy were taken, who were admitted for its artificial termination. Results. Inflammatory diseases of the lower genital organs in the group of women with bacterial infection of the fetal egg are significantly more common than in the group of viral infection of the fetal egg and the control group, and correlate with the results of pathomorphological studies in more than 86.7% of cases. In the group of women with bacterial infection, according to the results of the study of the structure of cervical mucus and the level of secretory IgA, a decrease in local immunity of the cervix was revealed. Conclusion. The analysis of the research results allows us to confirm the concept of ascending infection of the fetal egg in the bacterial etiology of undeveloped pregnancy, which deserves the practical attention of obstetricians and gynecologists and further study for the timely treatment of at hospital phase dysbiotic and inflammatory diseases of the lower parts of the female genital organs during pregravidar preparation.